PENGEMBANGAN UMKM DENGAN INOVASI PRODUK GULA AREN SEBAGAI UPAYA PENINGKATAN PENDAPATAN BAGI MASYARAKAT DESA CICADAS SUKABUMI - RR Amanna Dzikrillah Lazuardini Luqman Al Hakim; Salix Fini Maris; Rena Yuliana; Fuji Maulana; Ahmad Sahal Gojali; Rahmi Rahmawati Sayyidah; Sonya Pita Lestari (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2023)
The purpose of this real work or community service activity is to provide information and assist the bojong hamlet community, sugar palm processors, village-owned enterprises and the Cicadas village government, regarding the development of palm sugar as an alternative in increasing people's income. Real work lecture activities are carried out for a month. The activity began with the implementation of socialization in forming an understanding of superior village business, simulations of making Ants Sugar and assistance with marketing plans and targets. The results of this real work or community service activity are in the form of increasing understanding related to the potential of local natural resources and the main development of which is ant sugar, BUMDes has a plan to develop the Ant and Kolang Kaling Sugar Business. Meanwhile, the village government will support the development of ant sugar by issuing a village regulation that requires the consumption of local products, as one of the markets.